Comparative Exploration of Antioxidant Properties of Alcalase- and Trypsin-Hydrolyzed Porcine By-Products and Their Classification for Industrial Use - Jun Hwang; Woo-Young Son; Eun Ju Jeong; Kyeong-Soo Kim; Eui-Cheol Shin; Dong-Heon Song; Kyung-Woo Lee; Hyun-Wook Kim (Applied Sciences)
Porcine by-products have garnered attention as an excellent material for producing antioxidant peptides; however, understanding the antioxidant characteristics of protein hydrolyzates derived from specific parts remains limited. In this study, we compared the antioxidant properties of protein hydrolyzates derived from major porcine organs (heart, kidney, spleen, liver, and lung) and performed classification based on their antioxidative potential. Their chemical composition exhibited significant variations, with a high protein content ranging from 15.90 to 20.30 g/100 g. Alcalase achieved higher hydrolysis efficiency than trypsin, which induced limited degradation of some proteins, such as porcine serum albumin. The hydrolyzates exhibited superior radical scavenging activities compared to the raw materials, although their reducing power remained unaffected or, in some instances, decreased. Hierarchical and k-mean cluster analyses revealed distinct antioxidant profiles and Alcalase-hydrolyzed kidney and trypsin-hydrolyzed lung hydrolyzates were deemed the most promising candidates, with strong radical scavenging activities and reducing power. Our findings indicate that, even when processed in bulk rather than being obtained from specific parts, porcine by-products can produce hydrolyzates rich in antioxidant peptides through enzymatic hydrolysis. However, selectively processing porcine kidneys with Alcalase and lungs with trypsin is recommended to produce premium products with enhanced and balanced antioxidant properties.